2013
DOI: 10.1186/1479-5868-10-89
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ prospective screen time by gender and parental education, the mediation of parental influences

Abstract: BackgroundThe present study investigated associations in gender dyads of parents’ and adolescents’ time spent on television and video viewing (TV/DVD), and computer and electronic game use (PC/games) at the ages of 11 and 13 years. Possible mediating effects of parental modelling and parental regulation in the relationship between parental education and adolescents’ prospective TV/DVD and PC/game time were further examined.MethodsA total of 908 adolescents, participating at both ages 11 and 13 years in the Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
3
29
1
3
Order By: Relevance
“…Totland et al . found that maternal and paternal modelling were mediators of the relationship between parental education and TV/DVD viewing, but not for computer/game use. No mediating effect was found for parental regulation.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Totland et al . found that maternal and paternal modelling were mediators of the relationship between parental education and TV/DVD viewing, but not for computer/game use. No mediating effect was found for parental regulation.…”
Section: Resultsmentioning
confidence: 91%
“…Five additional studies were obtained through manual reference searching. A total of 37 studies were therefore included in this review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of parents’ screen time rule-setting has been shown to vary depending on the age of the children, parental age, and parental race [51, 52]. Moreover, it is important to consider screen time messages children receive from parents’ verbal communication and how these might differ from parents’ own actions [53].…”
Section: Introductionmentioning
confidence: 99%
“…As in most developed countries ( 9 – 11 ) , a significant proportion of Norwegian children and adolescents fail to meet national guidelines on diet and physical activity, eating fruit and vegetables too seldomly, consuming energy-rich and sugar-rich products too frequently, and failing to engage in the recommended 1 h of moderate-to-vigorous physical activity (MVPA) daily ( 12 ) . According to national data, sedentary activities like television viewing and computer use have also increased markedly among Norwegian children and adolescents over the last decade ( 13 ) .…”
mentioning
confidence: 99%